The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12030623
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Alterations in High Fat Diet Induced Obesity: Effects of Tart Cherry Seeds and Juice

Abstract: Evidence suggests that obesity adversely affects brain function. High body mass index, hypertension, dyslipidemia, insulin resistance, and diabetes are risk factors for increasing cognitive decline. Tart cherries (Prunus Cerasus L.) are rich in anthocyanins and components that modify lipid metabolism. This study evaluated the effects of tart cherries on the brain in diet-induced obese (DIO) rats. DIO rats were fed with a high-fat diet alone or in association with a tart cherry seeds powder (DS) and juice (DJS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 84 publications
(79 reference statements)
10
60
2
Order By: Relevance
“…Our results showed an increase of AQP4 in OZRs, similar to the results in the diet-induced obese rats [30], as well as in the animal model of hypertension [58]. Also, elevated expression of AQP4 was reported in the cerebral cortex of stroke-prone spontaneously hypertensive rat of 20 weeks and the spontaneously hypertensive rat of 32 weeks [58].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results showed an increase of AQP4 in OZRs, similar to the results in the diet-induced obese rats [30], as well as in the animal model of hypertension [58]. Also, elevated expression of AQP4 was reported in the cerebral cortex of stroke-prone spontaneously hypertensive rat of 20 weeks and the spontaneously hypertensive rat of 32 weeks [58].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in aging or in the presence of some diseases, the cerebral expression of GFAP and GFAP mRNA was higher [48,49]. Astrogliosis is common in the brain of spontaneously hypertensive rats and in streptozotocin-treated diabetic rats [49,50], two pathologies to some extent coexisting in OZRs and at the same time in a model of diet-induced obesity [30]. Data regarding the higher GFAP expression in OZRs are in agreement and corroborate the previous study [28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recently Lamb et al, (2020) also demonstrated the effect of tart cherry juice to reduce risk of recurrent gout flare (Lamb, Lynn, Russell, & Barker, 2020). Di Bonaventura et al, (2020) indicated that tract cherry has potential role to prevent obesity-related risk factors, especially neuroinflammation based on a rat model study (Di Bonaventura et al, 2020). In a mice model study Smith et al, (2019) found that cherry supplementation (5% and 10%) improved bone mineral density (BMD) and some indices of trabecular and cortical bone microarchitecture and they proposed that these effects were likely attributed to increased bone mineralization (Smith et al, 2019).…”
Section: Health Benefitsmentioning
confidence: 99%